Preoperative L1 and L2 paravertebral block is an effective postoperative analgesia for hip arthroscopy in a multimodal analgesic regimen - Ilkhchoui, Yashar (BMJ Publishing Group, 2013)
We describe the case of a 30-year-old woman with chronic hip pain secondary to avascular necrosis. She received preoperative L1–L2 paravertebral block for postoperative pain control after arthroscopic hip surgery. Preoperative paravertebral block at the level of L1–L2 provided an effective postoperative analgesia for hip arthroscopy when used in a multimodal approach.